Crosstalk between endoplasmic reticulum stress and multidrug-resistant cancers: hope or frustration - Qing, Bowen; Wang, Song; Du, Yingan; Liu, Can; Li, Wei (Frontiers in Pharmacology, 2023)
Endoplasmic reticulum stress (ERS) is a kind of cell response for coping with hypoxia and other stresses. Pieces of evidence show that continuous stress can promote the occurrence, development, and drug resistance of tumors through the unfolded protein response. Therefore, the abnormal ac-tivation of ERS and its downstream signaling pathways not only can regulate tumor growth and metastasis but also profoundly affect the efficacy of antitumor therapy. Therefore, revealing the molecular mechanism of ERS may be expected to solve the problem of tumor multidrug resistance (MDR) and become a novel strategy for the treatment of refractory and recurrent tumors. This re-view summarized the mechanism of ERS and tumor MDR, reviewed the relationship between ERS and tumor MDR, introduced the research status of tumor tissue and ERS, and previewed the prospect of targeting ERS to improve the therapeutic effect of tumor MDR. This article aims to provide researchers and clinicians with new ideas and inspiration for basic antitumor treatment.